The Utilisation of the Open Journal System (OJS) by Public High School Educators - Supriyanto; Aurellysa Berlian Santoso (Sahwahita: Community Engagement Journal, 2023)
In the process of ensuring the quality of education, teachers are required to carry out publications at certain ranks. However, teachers face various obstacles in the publication process. One of them is the adaptation of the use of technology in submitting articles on the “Open Journal System” page. The Unissula Mathematics Education service team targeted this problem by conducting a Workshop on Management of the Use of the Open Journal System (OJS) for teachers at SMA Negeri 1 Pegandon, Kendal Regency. This activity is carried out in a hybrid way, both challenge and offline. In terms of quality, several teachers at SMAN 1 Pegandon have submitted their articles in the journal http://jurnal.unissula.ac.id/index.php/jpsa.Quantitatively, this activity got the enthusiasm of many teachers. This is proven by the presence of teachers who exceed 80% in socialization activities.